The Effectivity of Nutrition Education Booklet on Knowledge, Fast-food Consumption, Calorie Intake, and Body Mass Index in Adolescents - Irfan Said; Anto J. Hadi; Saskiyanto Manggabarani; Ida Lestari Tampubolon; Endang Maryanti; Agnes Ferusgel (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: The prevalence of adolescent obesity is increasing worldwide with proportions varying from country to country or between geographical regions within a country. The purpose of this study was to determine the effect of nutrition education with booklet media on knowledge, fast food consumption, calorie intake, and body mass index (BMI) in adolescents.Subjects and Method: This was a quasy experiment with no control group. The study was conducted in Junior high school in Medan, North Sumatera. A sample of 31 adolescents was selected by purposive sampling. The dependent variables were knowledge, fast-food consumption, calorie intake, and BMI. The independent variables were booklet media. Means of knowledge, fast food consumption, calorie intake, and BMI before and after intervention was examined by t-test.Results: Mean of knowledge after intervention (Mean= 12.90; SD= 2.71) was higher than before (Mean= 8.77; SD= 1.54) and it was statisticaly significant (p<0.001). Mean of fast food consumption after intervention (Mean= 9.48; SD= 1.38) was lower than before (Mean= 10.03; SD= 1.16) and it was statistically significant (p= 0.007). Mean of calorie intake after intervention (Mean= 2735.12; SD= 1999.9) was lower than before (Mean= 2821.09; SD= 216.13) and it was statistically significant (p= 0.003). BMI after intervention (Mean= 26.58; SD= 2.49) was equal with before intervention (Mean= 26.81; SD= 2.49).Conclusion: Nutrition education with booklet improves knowledge, reduces fast food consumption, and reduce calorie intake.Keywords: nutrition education, booklets, knowledge, fast food, calorie, body mass indexCorrespondence: Irfan Said. Study Program in Nutrition, Health Institute Helvetia. Jl. Kapten Sumarsono 107 Medan, North Sumatera, Indonesia. Email: Irfansaid1357@gmail.com. Mobile: 085256780839.Journal of Health Promotion and Behavior (2020), 5(1): 11-17https://doi.org/10.26911/thejhpb.2020.05.01.02